Taxonomia e biogeografia de Coleocephalocereus Backeb. (Cactaceae), um gênero endêmico do Brasil - Lima, Jefferson Gomes (Universidade Estadual Paulista (UNESP), 2026)
Este trabalho está organizado em uma introdução geral e duas seções: a introdução geral, que contextualiza o estado da arte do gênero Coleocephalocereus e apresenta informações complementares que subsidiam as demais seções; (1) constituído por um artigo filogenético associado a uma sinopse taxonômica, que elucida as relações evolutivas dentro de Coleocephalocereus, contribuindo para a melhor compreensão e a correta delimitação de linhagens de cactos rupícolas endêmicos do Brasil; (2) constituído por um artigo de biogeografia que discute com base em modelos de biogeografia história a provável área ancestral do gênero, bem como os eventos relacionados aos processos evolutivos que explicam a atual distribuição do grupo. Nesta dissertação, são reconhecidas 13 espécies: C. aureus, C. buxbaumianus, C. decumbens, C. diersianus, C. dolichospermaticus, C. estevesii, C. fluminensis, C. goebelianus, C. insigniflorus, C. pluricostatus, C. purpureus, C. superbus e C. uebelmanniorum. Cerca de metade dessas espécies apresentam distribuição restrita e seis espécies já se encontram ameaçadas de extinção na lista oficial da IUCN. Ao final, há um anexo com um artigo de nomenclatura, no qual foi alterado o nome de uma das espécies aceitas (i.e., C. insigniflorus).

This work is organized into a general introduction and two sections: a general introduction, which contextualizes the state of the art of the genus Coleocephalocereus and presents complementary information that supports the other statements; (1) consists of a phylogenetic study coupled with a taxonomic synopsis, which clarifies the evolutionary relationships within Coleocephalocereus, contributing to a better understanding and more accurate delimitation of lineages of rupicolous cacti endemic to Brazil; (2) consists of a biogeographical study that, based on historical biogeography models, discusses the likely ancestral area of the genus, as well as the events associated with the evolutionary processes that explain the current distribution of the group.. In this study, 13 species are recognized: C. aureus, C. buxbaumianus, C. decumbens, C. diersianus, C. dolichospermaticus, C. estevesii, C. fluminensis, C. goebelianus, C. insigniflorus, C. pluricostatus, C. purpureus, C. superbus, and C. uebelmanniorum. Approximately half of these species have restricted distributions, and six are listed as threatened with extinction on the official IUCN Red List. Finally, there is an appendix with a nomenclature article, in which the name of one of the accepted species has been changed (i.e., C. insigniflorus).
Taxonomy and biogeography of Coleocephalocereus Backeb. (Cactaceae), a genus endemic to Brazil
Keywords: Taxonomia vegetal; Filogenia; Biogeografia; Plant taxonomists; Phylogeny; Biogeography